2016
DOI: 10.1109/tns.2016.2618009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spent Nuclear Fuel Imaging Using Multiple Coulomb Scattering of Cosmic Muons

Abstract: Cosmic ray muons passing through matter lose energy from inelastic collisions with electrons and are deflected from nuclei due to multiple Coulomb scattering. The strong dependence of scattering on atomic number Z and the recent developments on position sensitive muon detectors indicate that multiple Coulomb scattering could be an excellent candidate for spent nuclear fuel imaging. Muons present significant advantages over existing monitoring and imaging techniques and can play a central role in monitoring nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
(69 reference statements)
1
29
0
Order By: Relevance
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
See 3 more Smart Citations
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
“…To simulate MCS, Geant4 implements a non-Gaussian model that is validated with experimental data [15,21], and it is used in the paper as a tool to test the proposed GMTE algorithm. Due to the interest in using cosmic ray muons in spent nuclear fuel storage cask assay, uranium represents high-Z material, iron represents medium-Z material, and concrete represents low-Z material.…”
Section: Geant4 Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar application for mapping cultural heritage sites was proposed in the 1970s by L. W. Alvarez to inspect the Chefren pyramid for hollow vaults [11], and very recently implemented with spectacular results [12]. The technique has been successfully applied to volcano inspections to characterize the inner structures and lava domes [13][14][15][16][17], to mining [18], to archaeology [19], including tunnel searches [20], geological surveys [21,22], nuclear waste [23][24][25][26] and reactor monitoring [27,28].…”
Section: Introductionmentioning
confidence: 99%